The Effect of Hurdle Hops And Knee Tuck Jump Exercises in Terms of Leg Muscle Power on Freestyle Swimming Speed - Meliala, Reza Armada; Nurkadri, Nurkadri; Mahmuddin, Mahmuddin; Siregar, Yan Indra (Universitas PGRI Palembang, 2024)
This study aims to determine the effect of the Hurdle Hops and Knee Tuck Jump Training in terms of Leg Muscle Power on the Speed of Freestyle Swimming at a Distance of 50 Meters for Children Aged 12-13 Years at the PRIM Swimming Club in 2022. The research method used is an experimental method with one group pretest dan posttest design. The sampling technique used was purposive sampling at selayang swimming pool on PRIM Swimming Club Medan. The number of athlete samples used was 8 people. This research was carried out of exercise 3 (three) times a week ( 18 meets ). Hypothesis analysis using uji-t with pre-test data and post-test data for freestyle swimming improvement, where the results obtained from the analysis of tcount of 10 are then compared with the ttable value with dk = n-1 (8-1 = 7) at a significant level α = 0.05 is 1,895, thus t-count < ttable (0,99 < 1.8946). This means that Ho is rejected and Ha is accepted, so it can be concluded that there is not a significant effect of the Hurdle Hops and Knee Tuck Jump Training in terms of Leg Muscle Power on the Speed of Freestyle Swimming at a Distance of 50 Meters for Children Aged 12-13 Years at PRIM Swimming Club in 2022 . Keywords: Impact; Hurdle Hops; Knee Tuck Jump and Crawl Swimming